At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Assume Julie is x years old
(x+3)+x+(x-8)=55 Julie is 20 years old
3x-5=55 Janet is 23 years old
3x=60 brother is 12 years old
x=20
(x+3)+x+(x-8)=55 Julie is 20 years old
3x-5=55 Janet is 23 years old
3x=60 brother is 12 years old
x=20
Let us assume age of Julie to be x years this implies age of janet is (x + 3) years and age of Janet's brother is (x - 8) in this way we will solve for x and find out everyone's age.
How we are assuming and constructing ages from the given question and forming them into mathematical expressions ?
here we have taken x years for the person having least age for our convenience.Her sister is 3 years older than her so her age addition to 3 years.Her elder brother is 8 years younger than her sister so her sister's age less to 8 years.
in the given question sum of their ages is 55
So,
[ x + (x + 3) + (x - 8) ] = 55
3x - 5 = 55
3x = 60
x = 20
So, Julie's age is 20 years
Janet's age is 20 +3 = 23 years
Janet's brother's age is = 20 - 8 = 12 years.
Learn more about Age related word problems here :
https://brainly.com/question/91727
#SPJ2
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.